PROSECUTING CRIMES OR ATTEMPTING COLLABORATION: THE RELATIONSHIP OF THE COMMUNIST REGIME IN YUGOSLAVIA WITH ROMAN CATHOLIC BISHOPS IN CROATIA 1945–1951 (Heritage, 2025)
The research aims to explore the nature of the relationship between the Communist regime and the Roman Catholic Church in Croatia after World War II. From 1945 to 1951, the Communist leadership sought to establish favourable relations with Roman Catholic bishops despite their clergy’s involvement in Ustasha crimes. The Communists offered amnesty to the Church and its bishops, granting them more favourable treatment compared to other religious communities in Yugoslavia. In exchange, the regime expected loyalty and minimal criticism from the bishops. The regime inconsistently prosecuted war crimes and crimes against humanity committed during the fascist occupation. While continuing to commit crimes against innocent people, the regime used courts and prosecutors to reinforce its dictatorship. Offenses were handled differently depending on the individual's stance. Bishops who showed loyalty to Tito’s regime, such as Bishop Akšamović, were rewarded, whereas Archbishop Stepinac was sentenced for his criticism of the regime, despite being formally charged with supporting fascist authorities during the war.
Keywords: oman Catholic Church, War crimes, Josip Broz Tito, Communist Party of Yugoslavia, Alojzije Stepinac